CD8 helps TCR catch slippery self pMHC. (December 2018) - Dushek, Omer; Dustin, Michael
A new model proposes that an applied force allows the co-receptor CD8 and the kinase Lck to selectively stabilize TCR interactions with negatively selecting ligands, but not those with positively selecting ligands, during the negative selection of self-reactive thymocytes.